2009
DOI: 10.1073/pnas.0904346106
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of WASp is a key regulator of activity and stability in vivo

Abstract: The Wiskott-Aldrich syndrome protein (WASp) is a key cytoskeletal regulator in hematopoietic cells. Covalent modification of a conserved tyrosine by phosphorylation has emerged as an important potential determinant of activity, although the physiological significance remains uncertain. In a murine knockin model, mutation resulting in inability to phosphorylate Y293 (Y293F) mimicked many features of complete WASp-deficiency. Although a phosphomimicking mutant Y293E conferred enhanced actin-polymerization, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 42 publications
2
92
0
Order By: Relevance
“…46 Conversely, the inability to phosphorylate this site reduces WASp-dependent actin polymerization in vitro and in vivo, conferring a WASpdeficiency state. 46 In the present study, we have shown that despite normal serine phosphorylation, all WASp EMM and WASp dEVH1 showed reduced tyrosine phosphorylation in vivo and we hypothesize that this results from impaired WIP-mediated retention and spatial regulation at sites of actin polymerization. In addition, WASp EMM impaired the intrinsic regulation of WASp activity in vivo, as evidenced by increased total intracellular f-actin after stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Conversely, the inability to phosphorylate this site reduces WASp-dependent actin polymerization in vitro and in vivo, conferring a WASpdeficiency state. 46 In the present study, we have shown that despite normal serine phosphorylation, all WASp EMM and WASp dEVH1 showed reduced tyrosine phosphorylation in vivo and we hypothesize that this results from impaired WIP-mediated retention and spatial regulation at sites of actin polymerization. In addition, WASp EMM impaired the intrinsic regulation of WASp activity in vivo, as evidenced by increased total intracellular f-actin after stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Constitutive tyrosine phosphorylation at this residue enhances WASp activity in vitro, but also targets WASp for accelerated degradation, complicating studies of effect in vivo. 46 Conversely, the inability to phosphorylate this site reduces WASp-dependent actin polymerization in vitro and in vivo, conferring a WASpdeficiency state. 46 In the present study, we have shown that despite normal serine phosphorylation, all WASp EMM and WASp dEVH1 showed reduced tyrosine phosphorylation in vivo and we hypothesize that this results from impaired WIP-mediated retention and spatial regulation at sites of actin polymerization.…”
mentioning
confidence: 99%
“…Among WASp phosphotyrosines, tyrosine 291 (Y291) of WASp was previously shown to be the major site of WASp phosphorylation and to be critical for the activation of WASp effector function in T cells, i.e., actin polymerization (1,9). The necessity of WASp phosphorylation on Y291 for its ubiquitylation was demonstrated by biochemical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This phosphorylation site is critically involved in the activation of WASp in numerous cellular responses including proliferation, phagocytosis and especially the assembly of adhesion and chemotaxis structures. 38 Finally, these murine models have been successfully used for ten years to conduct preclinical trials evaluating somatic gene therapy as an alternative to transplantation. In fact, despite the advances in their diagnosis, the prognosis of WAS patients remains poor.…”
Section: 33mentioning
confidence: 99%